2018
DOI: 10.1007/s11356-018-1458-8
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite removal from contaminated water by precipitation of aluminum, ferrous and ferric (hydr)oxides

Abstract: Several methods to remove arsenic from water have been considered, including co-precipitation with Fe and Al (hydr)oxides. Such compounds are considered very effective to remove As from contaminated water due to strong bindings between them. Three Fe:Al molar ratios (100:0, 80:20, and 60:40) were used to synthesize aluminum, ferrous, and ferric (hydr)oxides by precipitation in water highly contaminated with arsenite (50 and 500 mg L). The method was very efficient for all treatments (> 93%) at the beginning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
3
12
0
2
Order By: Relevance
“…Actually, precipitates with Al were less stable than precipitates in Al absence (Table 4). Different results were found for arsenite [As(III)], which showed that Al enhanced the stability of precipitates from Fe(II) treatments (Vasques et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Actually, precipitates with Al were less stable than precipitates in Al absence (Table 4). Different results were found for arsenite [As(III)], which showed that Al enhanced the stability of precipitates from Fe(II) treatments (Vasques et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…All these authors dealt with co-precipitation of trace elements with Fe/Al (hydr)oxides from Fe(II) salts. Vasques et al (2018), however, did similar studies of As co-precipitation with Fe/Al (hydr)oxides, from both Fe(II) and Fe(III) salts. Their results revealed that Al increases the As stability only in precipitates from Fe(II) treatments.…”
Section: Stability Of Precipitatesmentioning
confidence: 70%
“…A coprecipitação ocorre quando diferentes elementos em solução precipitam simultaneamente (Ford, 2012;. Este processo se revelou altamente eficaz para a remoção de elementos-traço de soluções contaminadas através da coprecipitação com óxidos de ferro e alumínio Vasques et al, 2018aVasques et al, , 2018b.…”
Section: Introdução Geralunclassified
“…A mobilidade dos elementos-traço e a estabilidade dos óxidos de ferro coprecipitados podem ser avaliadas através de métodos de extração que simulam diferentes condições ambientais. Procedimentos de extrações sequenciais e testes de bioacessibilidade são métodos de custo relativamente baixo que indicam mecanismos de sorção e força de ligação entre elemento-traço e fase mineral Vasques et al, 2018a).…”
Section: Introdução Geralunclassified
See 1 more Smart Citation